Titration of intravenous synthetic oxytocin post vaginal birth following induction or augmentation - Lewis, L.; Hauck, Yvonne; Pemberton, A.; Crichton, C.; Conwell, M. (Elsevier Ltd, 2016)
Evidence exists for titration of intravenous oxytocin during induction and augmentation, whereas no evidence was identified for titration of intravenous oxytocin following vaginal birth, where management excluded oxytocin for postpartum haemorrhage (PPH). This retrospective cohort study explored this issue through patient case notes and computerised perinatal data. Analysis included 335 women comparing induction (n = 226, 67%) to augmentation (n = 109, 33%). The two groups differed in terms of: parity; oxytocin dosage; length of time on intravenous oxytocin; and the length of first and second stage labour. They had similar rates of PPH and titration of intravenous oxytocin following birth was rarely recorded.